2013
DOI: 10.1016/j.sysconle.2013.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Load balancing of dynamical distribution networks with flow constraints and unknown in/outflows

Abstract: We consider a basic model of a dynamical distribution network, modeled as a directed graph with storage variables corresponding to every vertex and flow inputs corresponding to every edge, subject to unknown but constant inflows and outflows. As a preparatory result it is shown how a distributed proportional-integral controller structure, associating with every edge of the graph a controller state, will regulate the state variables of the vertices, irrespective of the unknown constant inflows and outflows, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 15 publications
0
42
0
Order By: Relevance
“…Now, recall the multi-agent system (4) together with the output (7). Similar to Section 2.2, we first consider the open loop case where no external control input is applied to the agents.…”
Section: Problem Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Now, recall the multi-agent system (4) together with the output (7). Similar to Section 2.2, we first consider the open loop case where no external control input is applied to the agents.…”
Section: Problem Formulationmentioning
confidence: 99%
“…Another example of dynamical networks in which one seeks for disturbance rejection is balancing demand-supply in distribution networks; see e.g. [6,7]. In this framework, storage variables correspond to vertices, flow inputs corresponding to edges, disturbances amount for inflows and outflows at certain vertices, and the objective is to achieve load balancing, that is convergence of storage variables to the same value by regulating the flow inputs.…”
Section: Introductionmentioning
confidence: 99%
“…Under the given assumption that the cost functions P k are of Legendre type, the gradients ∇P k are invertible on the open sets {λ k : −λ k < λ k <λ k } [4]. Since the optimal solution must always be strictly feasible, the two optimality conditions (10) can be combined to…”
Section: Optimal Time-varying Routingmentioning
confidence: 99%
“…The aspect of balancing in distribution networks has been studied in [8] using a one-step model predictive control scheme. In [9], [10] distribution networks with constant supply and demand were considered and it was shown that the balancing problem can be formulated in a Hamiltonian framework.…”
Section: Introductionmentioning
confidence: 99%
“…In [9], using the same model as in [8], the authors focus on a different problem of driving the state to a small neighborhood of the reference value and relate the control input value at equilibrium to an optimization problem. In the current paper we will generalize most of the results of our previous work [10] to the case of arbitrary constraint intervals, making use of a new technique extending the graph to a graph with a larger number of edges admitting a coverage by nonoverlapping cycles. Section 6 contains the conclusions.…”
Section: Introductionmentioning
confidence: 99%